Pengaruh Media Sosial OME TV Terhadap Kepercayaan Dalam Interaksi Sosial (Studi Pada Mahasiswa Ilmu Komunikasi Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Mulawarman) - Syam, Hafitrah Amelia; Dwivayani, Kadek Dristiana; ., Nurliah; Kristian, Dony (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This research explores the influence of Ome TV social media on construction trust in social interactions of FISIP Communication Science students Mulawarman University. The contemporary digital era has changed platforms social media, presents significant challenges in building trust social through virtual interactions. Using a quantitative approach, research applying survey methods through distributing questionnaires to science students Communication. The research design was designed to analyze inter-correlation intensity of use of Ome TV and trust-forming variables digital interaction context. The research instrument was built systematically to measure dimensions connectedness, intensity of interaction, and perceived security of the virtual space. Analysis data is carried out using inferential statistical techniques to identify pattern and significance of relationships between variables. The main focus of his research is reveal the mechanisms of trust formation in social media interactions, taking into account the continuing complexity of online dynamics develop. Research views that every virtual interaction has potential to form dynamic trust constructs. His theoretical contribution lies in the development of the research conceptual framework digital communication, especially the dynamics of trust in virtual interactions. Practically, these findings are expected to provide an empirical basis development of safe, responsive and constructive social media platforms.